Living in Plain Sight: The Winnebago Struggle To Remain In Wisconsin During the Removal of 1863 - Ferries, Craig H. (My University, 2010)
The year of 1863 set the precedent on how the United States government, the State of Wisconsin and many of the local citizens dealt with the Winnebagos. The Winnebagos that attempted to remain in Wisconsin or those that returned to Wisconsin after the forced in many cases were victimized because there was no Winnebago Indian Agent within Wisconsin. In addition, 1863 set the precedent on how the United States government, the State of Wisconsin, and the local population interacted and dealt with each other over the issues concerning the Winnebagos. This paper will initially focus on governmental interaction with the Winnebagos on a federal, state and local level. Examples of this will be articles on meetings between Governor of Wisconsin Solomon and the Winnebago Chiefs that still reside in Wisconsin. Also, correspondence concerning the local populations and their open hostility toward the Winnebagos that lived near them. Secondly, this paper will focus on governmental interaction with each other concerning the Winnebagos. Examples of this are ongoing correspondence between Governor Edward Solomon, Commissioner Charles Mix and Major General Pope. The conclusion of the paper will focus on the reaction of the local populations of Wisconsin that interact with the Winnebagos. Examples of this are correspondence between Solomon and the local citizens in addition, to correspondence between Solomon and Pope concerning the local reaction to events and issues surrounding the Winnebagos.
Keywords: Indians of North America--Wisconsin--Relocation; Winnebago Indians--Government relations; Winnebago Indians--History--19th century; Winnebago Indians--Land tenure; Winnebago Indians--Relocation; Ho Chunk Indians--History